Jordan News Agency Journalists’ Perception of Media Ethics and its Relationship to Professional Practice - Al- Hailat, Khaled Mahmoud; Aljarrah, Ayah Adnan (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to assess the extent to which journalists at the Jordan News Agency (Petra) understand media ethics and their relationship to professional practice, as well as to identify their attitudes towards these ethics. Methods: The study sample was selected using the "available sample" method, consisting of 104 journalists working at the Jordan News Agency (Petra), who are members of the Jordanian Journalists Association. The study relied on the theories of social responsibility and the gatekeeping function of media, using a descriptive survey methodology and a questionnaire as the research tool. Results: The study found that the journalists at the agency have a high level of awareness of media ethics, a high degree of adherence to these ethics, and a high level of commitment to ethical practices. Conclusions: The study recommended granting journalists more freedom in their work, reducing pressures and interventions in their work and the operations of media institutions, encouraging them to keep up with technological advancements, and leveraging features such as interactivity and collaboration. It also suggested conducting more research on journalists’ understanding of media ethics and its relationship to professional practice.